SCIENCE LABORATORIES AND THE QUALITY OF OUTPUT FROM SECONDARY SCHOOL STUDENTS IN OYO STATE - Adeyemi, T. O. (Sokoto Educational Review, 2020)
This paper examined science laboratories and the quality of output from secondary schools in Ondo State, Nigeria The design was made along the lines of a descriptive survey while the study population comprised all the 257 secondary schools that presented candidates for the year 2003 senior secondary Certificate examinations in the State. The sample consisted of 168 secondary schools drawn randomly from the study population. The instrument used to collect data for the study was an inventory while the data collected were analysed using the one-way analysis of variance and Least Significant Difference test. Semi-structured interviews were conducted for principals and education officers while their responses were analysed through the content analysis technique. Die findings showed that the quality of output was best in schools having laboratories in three science subjects, Physics, Chemistry and Biology. The mean scores were highest in schools having three science laboratories. The interviewees’ responses agreed with the findings of the study. On the basis of the findings, it was recommended that Government should urgently provide laboratories in the three science subjects in schools with shortages of science laboratories.